Correction To: Effect of Mechanical Pre-Treatment on the Recovery Potential of Rare-Earth Elements and Gold From Discarded Hard Disc Drives (journal of Material Cycles and Waste Management, (2025), 27, 1, (257-269), 10.1007/S10163-024-02108-0 - Küçüker, Mehmet Ali; Habibzadeh, A.; Gökelma, Mertol; Kucuker, M.A.; Gökelma, M. (Springer, 2025)
In this article the affiliation details for Mertol Gökelma were incorrectly given as “Department of Environmental Engineering, İzmir Institute of Technology, Izmir 35433, Turkey” and should have been deleted. © The Author(s), under exclusive licence to Springer Nature Japan KK, part of Springer Nature 2024.